Pengaruh social media marketing, online customer review, dan religiusitas terhadap keputusan pembelian konsumen shopee di masa pandemi Covid-19 dengan minat beli sebagai variabel intervening - Ngadimen, Ahmad Nurrokhim; Widyastuti, Emy (Journal of Management and Digital Business, 2021)
The purpose of this study was to determine the effect of social media marketing, online customer reviews, and religiosity on Shopee consumer purchasing decisions during the Covid-19 pandemic, with purchase intention as an intervening variable. This type of research is a quantitative study with a population of Shopee consumers scattered randomly in Indonesia. The sampling technique in this study used purposive sampling, totaling 100 respondents. Method analysis data use path analysis. Statistical test results show that social media marketing, online customer reviews, and religiosity have no significant positive effect on purchasing decisions. Then social media marketing and online customer reviews have a positive and significant effect on buying interest, while religiosity has a positive and insignificant effect on buying interest. Buying interest can mediate the influence of social media marketing and online customer reviews on purchasing decisions. However, buying interest cannot mediate the influence of religiosity on purchasing decisions.